Perceiving and Reporting Domestic Violence Incidents in Unconventional Settings: A Vignette Survey Study - Aviram, Hadar (2012)
Domestic violence abuse is under-reported to police, but has long been viewed only through a lens of female oppression. Some literature suggests that in unconventional abusive relationships, such as in same-sex relationships or in relationships with a female batterer and male victim, the problem of under-reporting is more severe. This Article uses a vignette survey design to examine the tendencies to report such incidents to the police, by controlling for the type of relationship, the existence of outing threats, and the presence of mutual violence. Compared to the typical scenario involving a male batterer and female victim, we find significantly more unwillingness to contact the police in situations where women abuse men and in same-sex abuse scenarios. Violence in these alternative relationships is more often seen as mutual relationship problems that should be resolved through counseling and reconciliation. Also, we find that mutual violence leads to a decline in reporting only in the normative scenario. Conversely, in nontraditional relationships, the victim is less likely to be penalized for engaging in violence. Further, non-heterosexual respondents are less likely to report same-sex violent incidents. Finally, education, as well as residing in a more progressive state regarding same sex issues, yield lesser rates of police reporting